G533 Reducing the number of unnecessary liver function tests requested on the paediatric intensive care unit. (27th April 2016) - Sinitsky, L; Shepherd, D; Cooshneea, M; Brierley, J
Abstract : Context: This project was conducted on a Paediatric Intensive Care Unit (PICU) at a quaternary Children's Hospital. All the PICU nurses and doctors were involved in the project. Problem: Between January and October 2014 PICU was spending an average £23, 392 on blood tests per month. An audit in October 2014 showed that liver function tests (LFTs) were requested daily on most patients, even with previous normal results. More blood tests were being ordered than clinically indicated. Reducing the number of inappropriate blood tests would have clear financial benefit. Assessment of problem and analysis of its causes: A driver diagram identified three primary drivers for blood test requesting: decision-making, situational awareness and computer-based ordering. Decision-making for routine blood tests was the responsibility of the bedside PICU nurses on each night shift. The communication between the nurses and doctors was an identified secondary driver. Staff survey showed that routine tests were often ordered by the nurse without prior medical discussion. Intervention: The project's primary aim was to reduce unnecessary LFT requests on PICU over 6 months by implementing a blood test request form. The secondary aims were to reduce other unnecessary blood test requests, including full blood counts, coagulation screens and CRP. The blood test request form, a table of common investigations, aided discussion between the bedside nurse and doctor and provided documentation of the agreed tests. Study design: The project was conducted in three phases: construction, testing and implementation of the blood test form. PDSA cycles were used within each phase. Strategy for change: Phase one (Construction): PICU lead nurse and consultants were consulted and agreed the format. Phase two (Testing): the blood test form was tested on each night shift for two weeks. Feedback led to improved accessibility. Phase 3 (Implementation): began 1 st December 2014. Monthly results were communicated to staff by email and presented at departmental meetings. Staff survey at the first monthly review found infrequent form use. Feedback led to a preferred change in format. Two PICU nurse champions were engaged to provide bedside support, education and feedback. Reminder stickers were also placed by every bedside computer. Measurement of improvement: The primary and secondary outcome measures were the number of blood test requests made to the pathology department each month. In the 8-month period following implementation, there was a significant and sustained reduction in LFT requests (Figure 1 ) (1) Start of Phase Two: Construction of blood test form (2) Start of Phase Three: Implementation of blood test form). A similar pattern of reduction has also occurred for full blood counts, coagulation screens and CRP. Effects of changes: There was a sustained reduction in the number of blood tests requested on PICU, especially LFTs, with a saving in excess of £36, 000. Reducing the number of inappropriate blood tests showed clear financial benefit for PICU. PICU consultants were regularly asked to feedback if any important blood tests were missed as a balancing measure. During the project no concerns were raised. Lessons learnt: Early engagement and support from key stakeholders avoided conflict with the pathology department and guaranteed data sharing. It also provided the permission needed to change established structures such as ward rounds. Involvement of nurse champions resulted in ward staff feeling supported and valued, greater form usage and higher quality feedback. Message for others: Not to underestimate the importance of identifying the key stakeholders early and investing the time to engage them fully. Staff at ward level will find making change hard, especially if initially it fails, but knowledge of full senior support encourages staff to embrace change.